Responses to romidepsin in patients with cutaneous T-cell lymphoma and prior treatment with systemic chemotherapy. Issue 4 (3rd April 2018) - Duvic, Madeleine; Bates, Susan E.; Piekarz, Richard; Eisch, Robin; Kim, Youn H.; Lerner, Adam; Robak, Tadeusz; Samtsov, Alexey; Becker, Jürgen C.; McCulloch, William; Waksman, Joel; Whittaker, Sean
Abstract: Cutaneous T-cell lymphomas (CTCL) are a group of non-Hodgkin lymphomas that typically present in the skin but can progress to systemic involvement. The optimal treatment for patients who relapse from or are refractory to systemic chemotherapy remains unclear. Romidepsin is a potent, class-I selective histone deacetylase inhibitor approved for the treatment of patients with CTCL who have had ≥1 prior systemic therapy. Here, we present a subanalysis of two phase-2 trials (NCT00106431, NCT00007345) of romidepsin in patients with CTCL who had prior treatment with systemic chemotherapy. Patients with prior chemotherapy were able to achieve durable responses to romidepsin, and response rates were similar to those in patients who were chemotherapy naïve. Overall, no new safety signals emerged in patients who had received prior chemotherapy. The data presented here suggest that romidepsin is safe and effective in patients with CTCL who received prior systemic chemotherapy.